2016
DOI: 10.1080/01639625.2016.1241060
|View full text |Cite
|
Sign up to set email alerts
|

Criminal Poisoning and Product Tampering: Toward an Operational Definition of Malicious Contamination

Abstract: Malicious contamination' encompasses multiple crimes which have received little previous academic attention, including poisoning and product tampering. While these acts may seem easy to distinguish, there are many areas of overlap, and so before these crimes and those who commit them can be understood clear definitions must be introduced. The presence or absence of 14 behavioural variables is proposed as a way of distinguishing product tamperings from poisonings, with the empirical definition then tested on 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…This sample was taken from a larger dataset of malicious contamination incidents (n=384), composed of intentional poisonings, product tamperings, and incidents which fell in between these two categories. Poisonings and product tamperings can be said to exist on either end of a spectrum and have been fully defined elsewhere (Wilson & Kilbane, 2017) (Wilson & Kilbane, 2017), and incidents of product tampering were most numerous in this sample (n=69), there were also several cases of poisoning (n=7) and one intermediate case in this sample as well. Both poisoning and product tampering cases were included here as these acts are thought to occur on a continuum, and so considering such acts together provides a more complete understanding of the full spectrum of malicious contamination incidents.…”
Section: The Samplementioning
confidence: 83%
See 1 more Smart Citation
“…This sample was taken from a larger dataset of malicious contamination incidents (n=384), composed of intentional poisonings, product tamperings, and incidents which fell in between these two categories. Poisonings and product tamperings can be said to exist on either end of a spectrum and have been fully defined elsewhere (Wilson & Kilbane, 2017) (Wilson & Kilbane, 2017), and incidents of product tampering were most numerous in this sample (n=69), there were also several cases of poisoning (n=7) and one intermediate case in this sample as well. Both poisoning and product tampering cases were included here as these acts are thought to occur on a continuum, and so considering such acts together provides a more complete understanding of the full spectrum of malicious contamination incidents.…”
Section: The Samplementioning
confidence: 83%
“…This is consistent with previous works which have found that the media may underreport hoax cases (see Tishler, 2016). Other potential gaps in the data have been identified previously when studying contamination (Cremin, 2001;Wilson & Kilbane, 2017), and so it is imperative that any method of data analysis used with such a sample allow for the inclusion of new information as it become available. Indeed, the use of Bayes'…”
mentioning
confidence: 99%
“…Additionally, such knowledge was found to be more prevalent among poisoners (24%) than product tamperers (12%; Wilson and Kilbane, 2017). However, in cases where groups were responsible for the contamination incident, where the identity of the perpetrator remained unknown, or where information related to expertise was simply not reported, it was not possible to identify whether the perpetrator had any existing poison knowledge.…”
Section: Poison 'Expertise'mentioning
confidence: 99%
“…These crimes are often difficult to distinguish from one another, and so one of the primary goals of this PhD research was to develop clear definitions based on specific behaviours for, in particular, acts of product tampering and poisoning (see Wilson and Kilbane, 2016). In order to accomplish this, a database of all known cases of malicious contamination within the chosen timeframe needed to be compiled and examined.…”
Section: Project Overviewmentioning
confidence: 99%
“…The case study discussed herein describes the process of database construction used in Wilson and Kilbane (2016), which is believed to be the first piece of research to offer clear, empirically-based definitions of product tampering and poisoning crimes, but also provide an analysis of the behaviour of those who commit these acts. In order to accomplish these goals, a dataset was created of all malicious contamination incidents occurring from 1970 to 2011,…”
Section: Project Overviewmentioning
confidence: 99%